The study of spray characteristics by using video image processing - Mohammad, Ismail (2013)
This thesis deals with video image processing analysis study of gasoline ethanol blends as the fuel. The objective of this study is to study about spray characteristics. Investigation of these spray from three type of fuel mixture such as pure gasoline (E0), gasohol (E50) and pure ethanol (E100) at different pressure. The pressures used in this study are 10 MPa and 20 MPa. Spray characteristics focus only on spray penetration and spray cone angle. The video from previous experiment is using to compare. From the video, image is captured frame by frame from start time until finished injection. Time taken for the spray is from 0.03 s to 0.12 s. Video imaging has been analyzed and the result is compared according spray evolution. At the 10 MPa, for E0, produced spray penetration is 120.3 mm at 0.06 s and cone angle 2.89° as the accurate result because at that time are shows the overall spray image. E50, produced the penetration 142.2 mm and cone angle 8.31°. E100, produced over than 120.2 mm penetration while the cone angle is 3.99 °. At the high pressure, result shows for E0 is 131.5 mm penetration and 3.71° of cone angle. E50 shows the penetration length 149 mm and cone angle is 10.87° and for E100 show the penetration and cone angle are over 150 mm and 5.75°. Comparing these result indicate higher pressure better penetration and reduce the cone angle because the density of fuel are used is different. It can conclude the physical properties are related with the spray pattern.